The challenges for basic-level savings and loan cooperatives in Mexico - Lara Gómez, Graciela; Hurtado Maldonado, Jesus (Cooperativismo & Desarrollo, 2019)
This article addresses the predominant problems among the basic-level savings and loan cooperatives inMexico. These cooperatives are organizations that provide financial services and contribute to social improvements in poor regions, where traditional banking has little or no presence. It is proposed that the persistence of these organizations is threatened by various factors, including the lack of formalization of their management processes and the regulatory standards that limit their participation in the market. A theoretical perspective focused on social economy and a qualitative methodological approach is presented to answer the following question: What are the challenges that basic-level savings and loan cooperatives face in Mexico? This is the starting question with which to analyze the sector and a cooperative located in a town experiencing high economic lag. The results show that the challenges to be faced by the sector are linked to the need to show the disadvantages of the legislation, in order to seek its reform. In the cooperative studied, the challenges must be addressed with a vision of the future, promoting the continuity of the organization based on strategies that integrate its dual economic and social purpose.
Keywords: savings; cooperatives; challenges; management; loans; regulation